Myxobolus sp. Infection in Koi (Cyprinus carpio) in Tahuna, North Sulawesi - Zulkifli; Ayuda Dyah Nurekawati (Samakia : Jurnal Ilmu Perikanan, 2019)
Koi (Cyprinus carpio) are being widely cultivated in Tahuna, North Sulawesi. Myxobolus sp. was found to have infected koi with white nodules such as oval-shaped tumors that resemble rice grains on the gill filaments. Examination of parasites was carried out by conventional methods, whereas analysis of the results of the data was carried out by descriptive methods. From the results of the examination, obtained seven koi fish infected with Myxobolus sp. with a prevalence of 23.3%. Myxobolus sp. examined had spore sizes between 12-15 µm × 7-9 µm and polar capsules size between 6-8 µm × 2 - 4 µm. Morphologically, Myxobolus sp. which was found in Tahuna, North Sulawesi is identical to Myxobolus sp. in Blitar, East Java.